2010
DOI: 10.1007/s10815-010-9477-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole sheep ovary cryopreservation: evaluation of a slow freezing protocol with dimethylsulphoxide

Abstract: Purpose To evaluate a slow freezing method for whole ovary cryopreservation by evaluating effects of added cryoprotectant. Methods Sheep ovaries were isolated during surgery, flushed with either Ringer-Acetate or dimethylsulphoxide and cryopreserved by slow freezing. After rapid thawing, viability was assessed by ovarian in vitro perfusion, cell culture, histology and fluorescent live-dead assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
(75 reference statements)
2
15
0
Order By: Relevance
“…In the present initial feasibility study, the sample size was too small to be able to statistically compare the androgen secretion from DMSO-and RA-frozen ovaries. However, the androgen production from DMSO-preserved ovaries was higher from all individual ovaries indicating the benefits of DMSO-preservation also for the human ovary, as we have previously shown for the cryopreseved whole sheep ovary [28]. In that study, we showed satisfactory equilibration using the uncontrolled slow freezing protocol method as also applied in the present study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present initial feasibility study, the sample size was too small to be able to statistically compare the androgen secretion from DMSO-and RA-frozen ovaries. However, the androgen production from DMSO-preserved ovaries was higher from all individual ovaries indicating the benefits of DMSO-preservation also for the human ovary, as we have previously shown for the cryopreseved whole sheep ovary [28]. In that study, we showed satisfactory equilibration using the uncontrolled slow freezing protocol method as also applied in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…We applied an identical DMSO-cryoprotocol as described in our previous report on the sheep ovary [28] and in the first report on whole ovary cryopreservation in the human [12]. In the latter study, performed on premenopausal ovaries, follicular viability was about 75% and there was a normal histological appearance when examined by light microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The pig ovary is approximately 7.3 cm 3 , which is similar to the human ovary of 6.5 cm 3 , while the sheep has a volume of 1 cm 3 – only approximately one‐sixth of the human premenopausal ovary (Milenkovic et al. ). The larger volume of the pig ovary may pose some limitation to perfusion and CPA diffusion, and the current study results may be reflective of the potential issues of preserving the whole human ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro perfusion results demonstrated compromised ovarian function of the ovary after cryopreservation in PROH, when compared to fresh controls. In another study of the same research group, the sheep ovaries were cryopreserved using the same uncontrolled-rate slow freezing with DMSO (Milenkovic et al, 2011). The ovaries www.intechopen.com in control group were frozen without CPA.…”
Section: Sheepmentioning
confidence: 99%